2013
DOI: 10.1073/pnas.1219047110
|View full text |Cite
|
Sign up to set email alerts
|

Defects in IRE1 enhance cell death and fail to degrade mRNAs encoding secretory pathway proteins in the Arabidopsis unfolded protein response

Abstract: The unfolded protein response (UPR) is a cellular response highly conserved in eukaryotes to obviate accumulation of misfolded proteins in the endoplasmic reticulum (ER). Inositol-requiring enzyme 1 (IRE1) catalyzes the cytoplasmic splicing of mRNA encoding bZIP transcription factors to activate the UPR signaling pathway. Arabidopsis IRE1 was recently shown to be involved in the cytoplasmic splicing of bZIP60 mRNA. In the present study, we demonstrated that an Arabidopsis mutant with defects in two IRE1 paralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
172
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 53 publications
(60 reference statements)
11
172
0
Order By: Relevance
“…Mishiba et al (12) recently reported that RIDD is required for the ER stress tolerance in Arabidopsis. They showed that the mRNAs for a set of secreted proteins were degraded in response to ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mishiba et al (12) recently reported that RIDD is required for the ER stress tolerance in Arabidopsis. They showed that the mRNAs for a set of secreted proteins were degraded in response to ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mishiba et al (12) recently showed that IRE1 is also involved in RIDD, a process by which mRNAs encoding secreted proteins on membrane-bound ribosomes are degraded in response to stress. In addition, they identified several RIDD target mRNAs in Arabidopsis.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…3,12,13 In view of these findings, OsIRE1 may play other important roles in addition to OsbZIP50 mRNA splicing and its function may be species specific.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IRE1A and IRE1B function in RIDD (Mishiba et al 2013) as in other organisms. A broad range of mRNAs encoding secretory and membrane proteins are destabilized through RIDD in Arabidopsis.…”
mentioning
confidence: 99%